2014
DOI: 10.1242/dev.103416
|View full text |Cite
|
Sign up to set email alerts
|

Nkx2-5 regulates cardiac growth through modulation of Wnt signaling by R-spondin3

Abstract: A complex regulatory network of morphogens and transcription factors is essential for normal cardiac development. Nkx2-5 is among the earliest known markers of cardiac mesoderm that is central to the regulatory pathways mediating second heart field (SHF) development. Here, we have examined the specific requirements for Nkx2-5 in the SHF progenitors. We show that Nkx2-5 potentiates Wnt signaling by regulating the expression of the R-spondin3 (Rspo3) gene during cardiogenesis. R-spondins are secreted factors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 66 publications
2
65
0
Order By: Relevance
“…2C,D,G,H) and previous Wnt reporter studies (Alfieri et al, 2010;Cai et al, 2013;Cambier et al, 2014;Gillers et al, 2015) indicate that Wnt signaling persists as cushions grow and elongate into mature valves. To explore Wnt signaling dynamics during the cushion/valve expansion phase, we assayed Wnt activity by Lef1 immunostaining.…”
Section: Wnt Signaling Supports Avc Cushion Expansionmentioning
confidence: 66%
See 2 more Smart Citations
“…2C,D,G,H) and previous Wnt reporter studies (Alfieri et al, 2010;Cai et al, 2013;Cambier et al, 2014;Gillers et al, 2015) indicate that Wnt signaling persists as cushions grow and elongate into mature valves. To explore Wnt signaling dynamics during the cushion/valve expansion phase, we assayed Wnt activity by Lef1 immunostaining.…”
Section: Wnt Signaling Supports Avc Cushion Expansionmentioning
confidence: 66%
“…Wnt reporter transgenic mice suggest that canonical Wnt signaling is active in AVC and OFT cushion mesenchyme during this growth phase (Gitler et al, 2003;Alfieri et al, 2010;Klaus et al, 2012;Gillers et al, 2015;Cai et al, 2013;Cambier et al, 2014). Known mitogenic roles of Wnt/β-catenin signaling in other developmental contexts (reviewed by Niehrs and Acebron, 2012) further support a role for Wnt in cushion expansion.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Additionally, anatomical blocks were occasionally observed that prevented continuous AP propagation, but which could be synchronized by means of electrical stimulation. Genetically, the hECT expression of MYH6 (α-MHC), TNNT2 (cardiac troponin-T), GJA1 (connexin-43) and NKX2-5 , a transcription factor for cardiac mesoderm specification [245], was demonstrated to be upregulated relative to age-matched aggregates, moreover the expression levels in the hECTs were in the range expressed in fetal and adult tissue. MYH7 (β-MHC) expression was significantly upregulated in hECTs relative to age-matched aggregates but also significantly less than found in either fetal or adult human tissue.…”
Section: Human Engineered Cardiac Tissuementioning
confidence: 99%
“…The evidence that Shox2 interacts with Nkx2-5 directly and their substantial genome-wide co-occupancy provide a potential mechanistic explanation for the antagonistic function of Shox2. However, although the inhibitory effect of Nkx2-5 over Isl1, Tbx3 and Hcn4 has been documented (Cambier et al, 2014;Mommersteeg et al, 2007b;Prall et al, 2007), the cis-regulatory elements associated with these genes that mediate such effects remain to be characterized. It is unclear whether Nkx2-5 inhibits the expression of these pacemaker genes directly, although it inhibits cardiac progenitor genes directly (Watanabe et al, 2012).…”
Section: Shox2 As a Transcription Factor In Venous Pole Developmentmentioning
confidence: 99%